Study on the Failure of the Bolted Flange Connection Structure between Stages of Missiles (Rockets) under Transverse Impact Load - Tonghui Tian; Jiehong Yuan; Daokui Li; Qingwen Wang; Baisheng Chen (Shock and Vibration)
Based on the bolted flange connection structure between stages of the missiles, four experimental specimens are simplified and manufactured, and the transverse impact failure experiments of the drop hammer are designed and carried out in this study. During the experiments, a new signal sensor is designed to collect the data of the bolts force, and the response data such as the bolts force, the slotted displacement of the connecting interface, and the impact force are collected in the loading process. The sequential failure mechanism of the structure under transverse impact load is analyzed and demonstrated according to the experimental results and the measured data. Additionally, a finite element model to simulate the failure process of the connection structure has been established, and the precision of the model has been verified and validated according to the experimental results. Moreover, the comparison between the results of the experiments and the simulation shows that the precision of this model is reliable in the engineering.